The Expressive Unit of Constructionism: Kenneth Martin at Whittington Hospital - Sam Gathercole (British Art Studies, 2023)
In 1953, an exhibition of Kenneth Martin’s abstract mobiles was staged in a children’s hospital ward in North London. Having languished in the footnotes of the history of British constructionism, the exhibition is read in this article as a significant demonstration of the determination of artists connected with the movement to find a place and function for discrete and modestly sized artwork within post-war social space. A range of evidence is gathered towards piecing together a sense of the exhibition and realising its significance. Photographs made by Nigel Henderson and held in the Tate archive are among the material traces considered. His images are shown to articulate particular modes of spectatorship activated by the exhibition, and to locate the exhibition within post-war discourses of children and childhood. In addition, Kenneth Martin’s own writing is drawn upon towards establishing a sense of the constructionist artwork as being something that protects a form of autonomy while being open to an immediate environment and the social forces at play in that environment. This article proposes a new way of understanding British constructionism within an expanded field of post-war British art.